(untitled) (Research, Society and Development, 2021)
This research aimed to correlate the indicators of Primary Health Care in their structure components with those of the process and with the results in the municipalities of Mato Grosso, Brazil, from 2008 to 2015. This is an evaluative, quantitative, retrospective research with use of secondary data from information systems. A matrix is composed by components of the structure (potential population coverage) the process (medical consultation, home visit of doctor and nurse, referral to the specialist and request of clinical pathology exams) and the result (hospitalization rate due to sensitive causes). It was construct when primary care, the proportion of live births of mothers with seven or more prenatal consultations and the infant mortality coefficient) and the descriptive analysis and Spearman correlation coefficient (rho) were performed. The study found that population coverage remained high above 83% and the process indicators suggest an improvement in family health strategy, with a reduction of 63.13% in the average referral to a specialist and 49.71% in the request for clinical pathology exams. However, there was a 7.13% reduction in the average home visit during the study period. There is a correlation between the structure and process component and between structure and result. It has found that with the evolution of the Family Health Strategy (FHS), there were changes in some indicators of primary care, but it is not possible to state that there was a change in the care model.